(3caGjI GdeHJOi aj Md CdaGX GdCNVQjs - (3eMeO GdoeNJGQ Hf LhOIs; (3YHO GdQMef Hf eMeO GdUZjQ GdGNVQj, CHh RjO,J (B983 (3g` s
(3ChdgG (B:s
(3ajbhd GdYHO GdabjQ eMeO GdoeNJGQ Hf LhOI abO GdJeS efj HYV GdENhGf TQM oeNJUQ Ydi ebOeI GdCNVQj s
(3BNQgG (B:s
(3dGjSJOje Teg Cj GdWjH deG ajg ef s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B331s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs